Document type in the ISBN Statistics - Giordanino, Eduardo Pablo (Documentación de las Ciencias de la Información, 2011)
This paper studies the documental types used in the ISBN system of Spain and Argentina. It first describes how new technologies affect the registry of the book production of the publishing sector. Thereafter it considers the book’s definition of the legislation of both countries and the function of the national bibliographic control. Analyzes the statistic data of the Spanish and Argentine ISBN agencies about ebook production. Final remarks are related to the proposal of a new documental tipology for the registry of new formats and sources used in the digital publishing industry.
Keywords: ebook; ISBN; publishing industry; documental tipology.